SpheroMold: modernizing the hanging drop method for spheroid culture - Guimaraes, Ana Paula Pereira; Calori, Italo Rodrigo; Bi, Hong; Tedesco, Antonio Claudio (Frontiers in Drug Delivery, 2024)
The hanging drop method is a cost-effective approach for 3D spheroid culture. However, obtaining numerous spheroids in a limited area becomes challenging due to the risk of droplet coalescence, primarly during Petri dish handling. In this study, we describe a general method to fabricate a 3D printing-based support called SpheroMold that facilitates Petri dish handling and enhances spheroid production per unit area. As a proof-of-concept, we designed a digital negative mold which comprised 37 pegs within a 13.52 cm 2 area, and then printed it using stereolithography; the density of pegs can be adjusted according to user requirements. The SpheroMold was created by pouring the base and curing agent (10:1) (Sylgard ® 184 silicone) into the mold, curing it at 80°C, and then attaching it to the lid of a Petri dish. Our SpheroMold effectively prevented droplet coalescence during Petri dish inversion, enabling the production of numerous 3D spheroids while simplifying manipulation. Unlike conventional techniques, our design also facilitated a larger volume of culture medium per drop compared to a standard Petri dish, potentially decreasing the necessity for frequent medium exchange to sustain cellular health and reducing labor intensity.